(untitled) (CAHIERS MAGELLANES-NS, 2024)
Abstract: Tamil Nadu, located in southern India, has a rich religious history. Buddhism, though not as predominant as Hinduism, played a significant role in shaping the region's spiritual and cultural development. This article traces the growth and decline of Buddhism in Tamil Nadu from its introduction around the 3rd century BCE to its eventual decline by the 12th century CE. The early spread of Buddhism is attributed to the missionary activities of Emperor Ashoka and the patronage from various rulers and local chieftains, notably the Pallava and Chola dynasties. Archaeological evidence and literary contributions highlight the flourishing of Buddhism, particularly in centers like Kanchipuram and Nagapattinam. However, the rise of the Bhakti movement, the resurgence of Hinduism, and the shifting political environment led to the gradual decline of Buddhism in the region. Despite its decline, Buddhism's influence persisted through cultural and intellectual exchanges. The article also examines the modern revival efforts, particularly those initiated by Pandit Ayothi Doss and Dr. B.R. Ambedkar, which sought to reconnect with Tamil Nadu's Buddhist heritage. This historical survey into the religious, cultural, and political forces that have shaped the evolution of Buddhism in Tamil Nadu.